A Study on the Clinico-serological Features of Nail Psoriasis - Ratnika; Mohammad Adil; Syed Suhail Amin (Indian Dermatology Online Journal)
Introduction: Nail psoriasis is a relatively unexplored clinical feature in the Indian population. Its correlation with cutaneous, musculoskeletal, and serological manifestations was analyzed. Material and Methods: This study included 45 patients with clinically evident nail psoriasis. Clinical characteristics, Psoriasis Area and Severity Index (PASI), Nail Psoriasis Severity Index (NAPSI), Nail Psoriasis Quality of Life Index 10 (NPQ10) scores and serological markers, Erythrocyte Sedimentation Rate (ESR), C-reactive protein (CRP), and Rheumatoid Arthritis factor (RA factor) were documented, calculated, and assessed to study their correlation. Results: Mean age was 35.36 ± 13.26 years. Mean NAPSI and NPQ10 were 41.96 ± 29.38 and 5.44 ± 5.31, respectively. Common nail findings were onycholysis (80%), subungual hyperkeratosis (75.5%), and pitting (62.2%). Joint involvement was seen in 31.11% of patients. Positive associations of NAPSI with duration of illness (P < 0.001, β = 0.57) and PASI scores (P < 0.001, β = 0.56) were observed. NPQ10 demonstrated associations with NAPSI (P < 0.001, β = 0.83) and PASI (P = 0.001, β = 0.83). Elevated ESR and CRP levels were associated with higher NAPSI scores (P < 0.001, β = 0.55, and P = 0.003, β = 0.43, respectively). Furthermore, duration of illness, NAPSI, and NPQ10 scores were positively correlated with joint involvement (P < 0.05). Conclusion: A strong correlation between nail psoriasis severity, disease duration, skin involvement, and nail-specific quality of life was observed. Furthermore, severe nail psoriasis was linked to a higher likelihood of joint involvement and elevated serological markers. These findings emphasize the importance of integrated treatment strategies for affected patients.